2018
DOI: 10.1542/peds.2017-4161
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Parent-Reported Autism Spectrum Disorder Among US Children

Abstract: To estimate the national prevalence of parent-reported autism spectrum disorder (ASD) diagnosis among US children aged 3 to 17 years as well as their treatment and health care experiences using the 2016 National Survey of Children's Health (NSCH). METHODS: The 2016 NSCH is a nationally representative survey of 50 212 children focused on the health and well-being of children aged 0 to 17 years. The NSCH collected parentreported information on whether children ever received an ASD diagnosis by a care provider, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
208
3
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 321 publications
(225 citation statements)
references
References 50 publications
7
208
3
7
Order By: Relevance
“…First, the survey was based on caregiver report of ASD, without clinical validation and data are limited by parents' knowledge and recollection, which could impact the validity of the results as reflecting the true priority needs of those with ASD. While not the gold standard in ascertainment, several large scale family caregiver surveys have used caregiver report of official diagnosis and other variables [Kogan et al, 2008[Kogan et al, , 2009Lin, Yu, & Harwood, 2012;Totsika et al, 2011;Shattuck, Narendorf et al, 2012] and a verification study showed reliability of diagnosis by caregivers [Daniels et al, 2012]. Second, our data was collected by convenience sampling using primarily online methods, which may have created barriers to participation for some families.…”
Section: Discussionmentioning
confidence: 99%
“…First, the survey was based on caregiver report of ASD, without clinical validation and data are limited by parents' knowledge and recollection, which could impact the validity of the results as reflecting the true priority needs of those with ASD. While not the gold standard in ascertainment, several large scale family caregiver surveys have used caregiver report of official diagnosis and other variables [Kogan et al, 2008[Kogan et al, , 2009Lin, Yu, & Harwood, 2012;Totsika et al, 2011;Shattuck, Narendorf et al, 2012] and a verification study showed reliability of diagnosis by caregivers [Daniels et al, 2012]. Second, our data was collected by convenience sampling using primarily online methods, which may have created barriers to participation for some families.…”
Section: Discussionmentioning
confidence: 99%
“…, Centers for Disease Control and Prevention (CDC), , , Kogan et al . , Nassar ). A systematic review of global prevalence rates estimates the prevalence of autistic disorder at 17 per 10 000 (Elsabbagh et al .…”
Section: Introductionmentioning
confidence: 99%
“…The main symptoms fall into a triad of problems with communication, social skills and restricted interest/repetitive behaviours (Volkmar et al 2004). The prevalence of ASC is thought to be around 0.5-1% (Kogan et al 2009). Around 60-70% of people with ASC also have intellectual disability (Brugha et al 2009).…”
Section: Introductionmentioning
confidence: 99%